A Study on the Researcher’s Perception Survey for Facilitating International Joint Research - Noh, Younghee; Shin, Youngji (International Journal of Knowledge Content Development & Technology, 2019)
In this study, we wanted to investigate and analyze the current status of international joint research conducted on researchers who have actually conducted or are doing international joint research and to identify difficulties in promoting international joint research based on this study and propose ways to promote future international joint research. As a result, autonomy of research subjects needs to be guaranteed for the revitalization of international joint research, establishment of international joint research guidelines and contract legal infrastructure, simplification and unification of administrative work system and supplementation of performance-related regulations will be necessary. URL: http://ijkcdt.net/xml/21162/21162.pdf